Exploring Co-Regulation as a Solution to Automated Disinformation in Kenya (Journal of Intellectual Property and Information Technology Law (JIPIT), 2023)
This paper discusses automated disinformation on social media in Kenya and its impact on democracy. Automated disinformation refers to disinformation that is exacerbated by the use of Artificial Intelligence (AI) and related emerging technologies, including algorithms and bots. The paper considers the electoral process in Kenya as a case study to highlight the threats that automated disinformation poses to the democratic process and proposes co-regulation as the way forward. Specifically, it reviews the impacts of automated disinformation on democracy including the negative effect on the availability of reliable and accurate information to enlighten the social media users’ political choices and the effect on the exercise of political will, public opinion, and democracy. The objective of this research is to provide policy recommendations to the relevant stakeholders on tackling the challenge of widespread automated disinformation perpetuated by social media users in Kenya whilst respecting fundamental human rights and promoting democracy. The author discusses the regulatory framework applicable to the information disorder phenomenon including those relevant to the exercise of the freedom of expression and access to information, noting that these rights play a significant role in strengthening democracy. This paper also considers the nascent regulation of AI and undertakes an analysis of how effective regulation can counter the widespread automated disinformation on social media platforms.